Part 3: Politics, Resistance, Alliances, and Imbroglios - Brochu-Ingram, Gordon Brent; Hobbs, Peter; Sandilands, Catriona (UnderCurrents: Journal of Critical Environmental Studies, 2015)
This is a portion of a roundtable discussion on queer ecologies held on 11 September 2014. The roundtable is also available as a podcast and was produced in collaboration with CoHearence, an initiative of graduate students in the Faculty of Environmental Studies suppored by NiCHE (Network in Canadian History and Environment).